Kesalahpahaman Euthanasia Dalam Perspektif Human Rights dan Hukum Islam - Alvian, Muhammad Andri; Kasim, Aksah; Pransisto, Johamran (Jurnal Litigasi Amsir, 2023)
Euthanasia is a new breakthrough that has its own existence in the world of medicine. Euthanasia is meant to be the act of deliberately eliminating human life to end the suffering it experiences. This paper aims to provide an overview of euthanasia and describe misconceptions in euthanasia practice. The method used in this study is literature research, the main focus of this research is on normative approaches including Islamic law, as well as using secondary data from literature containing information about euthanasia itself. The results of this study show that there is a misunderstanding in the practice of euthanasia, starting from the concept of human rights that does not accommodate the right to die as contained in article 28I paragraph (1) of the 1945 NRI Constitution, the prohibition of killing intentionally or unintentionally in the Criminal Code and the code of ethics which is oriented towards the obligation of a doctor to protect the life of a patient. In addition, judging from Islamic law, eliminating life by euthanasia is a suicide attempt that is not justified in Islamic law, let alone containing a very complex hypocrisy.